Design of Appropriate Waste Management in Abuja Satellite Towns - Felix Omongbale; Emmanuel Oluwadamisi (Indonesian Journal of Conservation, 2023)
Solid waste and its management have been of major concern to Abuja and its Satellite Towns. Improper management of solid waste has been a major avenue for disease transmission globally. This study examines the assessment of solid waste management systems in Abuja satellite towns within different socio-economic groups, and design of appropriate solutions for its management. In total 257 questionnaires were administered to residents in the 50 selected households across all the socio-economic groups. The data was analyzed using Statistical Package for Social Science (SPSS) 2020 and Microsoft Excel 2010. A total of 350 samples were collected from the households using random sampling to determine the amount of solid waste generated during one week in June 2021. The quantity generated was 1091.1kg with generation rates of 0.623kg/capita/day. The study recommended amongst others improvement on the present system of managing solid waste, and design of manual sanitary landfill as disposal solutions.